Earthquake Response Analysis of Tall Reinforced Concrete Chimneys considering Eccentricity. (11th March 2020) - Jiang, Yingchun; Liu, Tielin; Bai, Yikui
Abstract : A numerical algorithm is presented to analyze earthquake response of tall reinforced concrete (RC) chimneys based on stick multidegree-of-freedom models. The algorithm considers the eccentricity phenomena between spatial discrete nodes and corresponding centroids of investigated lumps. The spatial discrete segments of the chimney are used to construct the investigated lumps. The equations of dynamic equilibrium of the investigated lumps are derived, and the numerical calculation procedure is implemented. Phenomena of eccentricity are studied for 150 m and 210 m RC chimneys. Seismic stresses and effects of vertical ground motion for the two chimneys are also studied. Numerical results show that the tensile and compressive stresses of the seismic control cross sections of the chimneys may increase under the actions of several specific earthquake waves by considering existing eccentricities. The effect of eccentricity on the earthquake responses of tall RC chimney should be considered, and stresses caused by vertical ground motion should not be neglected to obtain accurate earthquake response of chimneys.